Covid-19 among the population deprived of liberty in Brazil and in the state of Paraná (Research, Society and Development, 2021)
The aim of this study was to compare Covid-19 incidence and mortality among population deprived of liberty (PDL), prison staff and general population in Brazil and in the state of Paraná. The methods consisted in data collection from weekly reports from the Nacional Justice Board and Health Ministry, between June and December 2020. Covid-19 testing, infection, mortality, and lethality rates were compared among PDL, prison staff and Brazil and Paraná’s general population. As for the results, compared to the general population, the relative risk of Covid-19 confirmed case among PDL was 1.594 (CI 95% 1.578 – 1.610) in Brazil and 3.055 (CI 95% 2.941 – 3.173) in Paraná. The proportion of test per national population was 22.86%, 44.42% and 4.45% among PDL, prison staff and general population, respectively. In Paraná, the testing rate was 8.19% in PDL, 42.98% in prison staff and 12.70% in the general population. In conclusion, the proportion of Covid-19 cases is greater in prisons than in the general population and the testing of PDL should be amplified.